Nest placement accounts for thermal exposure secondarily: insights on multifarious selection - Harris, Jonathan P.; McMurry, Scott T. (Frontiers in Ecology and Evolution, 2024)
IntroductionMultifarious selective pressures can interact to affect species’ life history evolution, with predation and thermal exposure as selective pressures for nesting birds. Gray Vireos (Vireo vicinior) seemingly nest on the periphery of their nesting substrate because of lower predation rates, thereby increasing exposure to weather. We explored how nest placement and vegetation structure can be used to account for the increased weather exposure that Gray Vireos experience when nesting on the periphery of the nesting substrate to avoid predation.MethodsFor each Gray Vireo nest, we placed temperature and light data loggers at three locations: at the nest site, at the opposite orientation of the nest within the nesting tree, and at the same orientation of the nest but in an adjacent tree. To measure nest orientation, we recorded the inverse compass azimuth (+/−1°) from the nest toward the trunk of the nesting tree, while accounting for declination. Nest temperatures and light exposure were compared across various dimensions of nest placement.ResultsThe orientation of nests was cooler than the opposite orientation in the mornings and in the late afternoons. When nests were placed in hotter orientations (e.g., south- or west-facing), nests surrounded by more foliage or placed closer to the interior of trees could compensate for the increased exposure.DiscussionOur findings suggest Gray Vireos accounted for the increased thermal exposure that comes from predator avoidance by using secondary dimensions of nest placement. Specifically, nests could be placed in orientations with cooler temperatures or in hotter orientations with greater shade potential. These results highlight how the interactive selection pressures of predation risk and microclimate can be tiered and shape life-history characteristics of birds.